EFEKTITIVITAS PROGRAM KELUARGA BERENCANA KELURAHAN LALEBATA KECAMATAN PANCA RIJANG KABUPATEN SIDENRENG RAPPANG - Yulia Izzah Annisa; Hariyanti Hamid; Pratiwi Ramlan (JIA: Jurnal Ilmiah Administrasi, 2022)
This study aims to determine the effectiveness of the family planning program in Lalebata Village, Panca Rijang District, Sidenreng Rappang Regency. The population in this study were 983 community leaders in the Lalebata village where the sampling used was purposive sampling as many as 98 people. The type of this research is descriptive quantitative, using data collection techniques through observation, questionnaires (questionnaire), and literature study. The data analysis is descriptive statistical. The results of this study indicate that the effectiveness of the family planning program in the Lalebata village can be categorized as less effective with a percentage of 60%, while the factors that affect the effectiveness can be categorized as less effective with a percentage of 60%.